Green Technologies Bridging Conventional Practices and Industry 4.0 - Foo, Dominic; Show, Pau Loke; Gopakumar, Suchithra (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Green technologies can be identified as key components in Industry 4.0. The scope of this book is to address how conventional green technologies can be a part of smart industries by minimizing waste, maximizing productivity, optimizing the supply chain, or by additive manufacturing. This theme focuses on the scope and challenges of integrating current environmental technologies in future industries. This book, "Green Technologies: Bridging Conventional Practices and Industry 4.0", aims to incorporate and introduce the advances in green technologies to the cyber-based industries. It is hoped that the novel green technologies presented in this book are useful in assisting the global community in working towards fulfilling the Sustainable Development Goals.